Sub-Saharan Africa : Forging New Trade Links with Asia - Gupta, Sanjeev (International Monetary Fund, 2007)
What is the impact on trade in sub-Saharan Africa of the recent rapid growth in China and other Asian countries, and the associated commodity price boom? This paper looks at how trading patterns (both destinations and composition) are changing in sub-Saharan Africa. Has the region managed to diversify the products it sells from commodities to manufactured goods? Has it expanded the range of countries to which it exports? And what about the import side? The time is ripe for sub-Saharan African countries to climb up the value chain of their commodity-based exports and/or achieve an export surge based on labor-intensive manufacturing.